PERAN ORANG TUA TERHADAP PERKEMBANGAN SOSIAL EMOSIONAL ANAK USIA DINI DI TK ISLAM PRAJAMUDA - Siti aisyah siti aisyah; Nihwan nihwan nihwan (Early Childhood Teacher Education Department UNIVERSITAS SULTAN AGENG TIRTAYASA, 2023)
The family environment is the initial environment of the child, all the behavior and development of the child is imitated by both parents. If parents are able to set a good example and role model for their children, then the child's attitude is not much different from that of the parents. Vice versa, if parents cannot be a good example, parents cannot expect their children to be better and fulfill the wishes of their parents. Based on the background described above, the formulation of the problem can be concluded in this research, namely: